Re-membering a Queer Body - Holmes, Morgan (UnderCurrents: Journal of Critical Environmental Studies, 1994)
In the spring 1993 issue of The Sciences, Brown University geneticist Anne Fausto-Sterling, citing the work of John Money, indicates that approximately four percent of the population is, to some degree, intersexual: they either possess physical characteristics of both officially recognized sexes or they have chromosomes which indicate a sex which are 'contradicted' by their physical appearance.1 In Toronto, the four percent figure translates into roughly 88,000 people. Yet little has been written about intersexuality, although its concerns often intersect with those of feminist and queer theory. This paper deals with feminist issues in patriarchal medicine and its relation(s) to intersexuality (and intersexuality's inherent ability to challenge arguments for the 'natural' basis of heterosexuality).
Keywords: 1900-1999; 1990-1999; LGBTQIA2+; amériques; approches et analyses; canada; cours; discipline; féminisme matérialiste; intersexuation; ontario; personnes intersexes; premier cycle; périodes historiques; régions géographiques; sciences humaines; soc2014; sociologie; thématiques; toronto; violences médicales

Nomadic subjects: Embodiment and sexual difference in contemporary feminist theory - Braidotti, Rosi (Columbia University Press, 1994)
Nomadic Subjects plaide pour un nouveau type de pensée philosophique, qui inclurait les idées du féminisme et abandonnerait le mode hégémonique qui est conventionnellement adopté dans la haute théorie. La prose personnelle, surprenante et vivante de Braidotti insiste sur une intégration du féminisme dans le discours dominant. Les essais explorent les problèmes qui sont au cœur des débats féministes actuels, y compris la relation de l'épistémologie occidentale à la «question de la femme», le féminisme et l'éthique biomédicale, le féminisme européen et la façon dont les féministes américaines pourraient se rapporter aux mouvements européens.
Keywords: LGBTQIA2+; cours; discipline; europe; fem1000; genre; har4600; identités LGBTQIA2+; philosophie politique; post-structuralisme; premier cycle; régions géographiques; sciences humaines; soc2014; thématiques; épistémologie

Feminities, masculinities, sexualities: Freud and beyond - Chodorow, Nancy J. (The University Press of Kentucky, 1994)
La psychanalyse peut-elle aller au-delà d'une vision monolithique du genre et de la sexualité normale pour aborder les questions de diversité et de variabilité dans le développement du genre et l'identité de genre ? Ses praticiens et théoriciens peuvent-ils rendre des comptes rendus non pathologisants de la variation de l'orientation sexuelle ? S'appuyant sur une lecture attentive des textes psychanalytiques commençant par Freud et sur sa propre expérience clinique, Chodorow [soutient] que la psychanalyse doit encore démêler la domination masculine de l'hétérosexualité. Elle démontre également le manque de compréhension psychanalytique de l'hétérosexualité et la polarisation problématique des sexualités normales et anormales. Chodorow soutient que la psychanalyse doit prêter attention à la spécificité individuelle et au cadre personnel, culturel et social
Keywords: 1900-1999; amériques; approches et analyses; cours; discipline; domination masculine; fem1000; genre; hétérosexisme; hétérosexualité; identités LGBTQIA2+; premier cycle; psychanalyse; périodes historiques; ressource en ligne; régions géographiques; sciences humaines; sexualité; systèmes d'oppressions; thématiques; états-unis

La peur de l'autre en soi: du sexisme à l'homophobie - Dorais, Michel; Dutey, Pierre; Welzer-Lang, Daniel (VLB, 1994)
Qu’est-ce que l’homophobie ? C’est l’appréhension de cette femme qui sommeille en chaque homme, de cet homme qui dort en chaque femme, de cet homosexuel ou cette homosexuelle qui, sait-on jamais, n’attend peut-être qu’à s’éveiller en nous.
Section: 302 pages : illustrations ; 23 cm
Keywords: 1900-1999; 1980-1989; 1990-1999; LGBTQIA2+; amérique du nord; amériques; approches et analyses; canada; cours; discipline; homophobie; hétérosexisme; identités LGBTQIA2+; premier cycle; périodes historiques; queer; québec; régions géographiques; shm4000; systèmes d'oppressions; thématiques

New feminist criticism: art, identity, action - Frueh, Joanna; Langer, Cassandra; Raven, Arlene; Frueh, Joanna; Langer, Cassandra; Raven, Arlene (IconEditions, 1994)
This anthology of fifteen timely articles offers a wide range of feminist criticism sparked by ideas and events of the 1980's and 1990's. The articles consider culture, language, race, identity, sexuality, gender, creativity, aging and other issues. Though different in methodology, the writings are united by their common interest in feminism as a vehicule for intellectual exploration and individual communication and understanding. In their revisionary approaches, the contributors offer exciting new insights into the complex interaction between women and cultures, questionning inclusion as well as exclusion. "New Feminist Criticism" presents the unfinished and ongoing agenda of feminism in art, society and culture.
Keywords: 1900-1999; 1980-1989; 1990-1999; LGBTQIA2+; approches et analyses; art contemporain; art féministe; arts; corps; cours; critique d'art; discipline; har4600; histoire de l'art; histoire et politique; identités LGBTQIA2+; intersectionnalité; premier cycle; périodes historiques; race; thématiques; vieillesse

The Heterosexual Imaginary: Feminist Sociology and Theories of Gender - Ingraham, Chrys (Sociological Theory, 1994)
This essay argues that the material conditions of capitalist patriarchal societies are more integrally linked to institutionalized heterosexuality than they are to gender. Building on the critical strategies of early feminist sociology through the articulation of a materialist feminist theoretical framework, the author provides a critique of contemporary sex-gender theory. She argues that the heterosexual imaginary in feminist sociological theories of gender conceals the operation of heterosexuality in structuring gender and closes off any critical analysis of heterosexuality as an organizing institution.... every sociological concept and thesis, as well as the overall patterning of these concepts and theses, is potentially open for reconsideration... With the emergence of feminist sociological theory, the critical emphases in sociology are strengthened by an insistence that sociological work be critical and change-oriented... in an intensely reflexive way towards sociology itself (Lengermann and Niebrugge-Brantley 1990:318). We must produce a political transformation of the key concepts, that is of the concepts which are strategic for us (Wittig 1992:30).
Keywords: LGBTQIA2+; approches et analyses; capitalisme; cours; discipline; féminisme matérialiste; histoire et politique; hétérosexisme; hétérosexualité; patriarcat; premier cycle; sciences humaines; sexualité; soc2014; sociologie; systèmes d'oppressions; thématiques

Paradoxes of gender - Lorber, Judith (Yale University Press., 1994)
In this innovative book, a well-known feminist and sociologist challenges our most basic assumptions about gender. Judith Lorber argues that gender is wholly a product of socialization, subject to human agency, organization, and interpretation, and that it is a social institution comparable to the economy, the family, and necessity of gender, she envisions a society structured for equality, where no gender, racial, ethnic, or social class group is allowed to monopolize positions of power.
Keywords: 1900-1999; amériques; approches et analyses; cours; discipline; fem1000; genre; identités LGBTQIA2+; premier cycle; périodes historiques; queer; ressource en ligne; régions géographiques; sciences humaines; sciences sociales; socialisation; sociologie; thématiques; états-unis

Sodomites, invertis, homosexuels: perspectives historiques - Mendès-Leite, Rommel (Cahiers Gai-Kitsch-Camp, 1994)
Section: 193 pages : illustrations ; 21 cm
Keywords: 1900-1999; LGBTQIA2+; approches et analyses; cours; discipline; discours dominant; europe; france; histoire et politique; hétéronormativité; hétérosexisme; identités LGBTQIA2+; premier cycle; périodes historiques; queer; régions géographiques; sexualité; shm4000; systèmes d'oppressions; thématiques

L'illusion transsexuelle - Mercader, Patricia (L'Harmattan, 1994)
Naît-on transsexuel ou le devient-on? Quel est le sexe des transsexuels? Peut-on parler de droit à l'identité sexuelle?.... En confrontant les points de vue des acteurs sociaux engagés dans le "phénomène transsexuel" (médecins, psychanalistes, sociologues, juristes et bien sûr les transsexuels eux-mêmes), cela éclaire les enjeux de société que traduisent ces questions profondément éthiques.
Section: 297 pages
Keywords: 1900-1999; 1980-1989; 1990-1999; LGBTQIA2+; approches et analyses; corps; cours; discipline; europe; france; hétérosexisme; identités LGBTQIA2+; postmodernisme; premier cycle; périodes historiques; queer; régions géographiques; sexe/genre; shm4000; systèmes d'oppressions; thématiques; transféminisme

The Politics of Inside/Out: Queer Theory, Poststructuralism, and a Sociological Approach to Sexuality - Namaste, Ki (Sociological Theory, 1994)
This paper outlines the main tenets of poststructuralism and considers how they are applied by practitioners of queer theory. Drawing on both Michel Foucault and Jacques Derrida, queer theory explores the ways in which homosexual subjectivity is at once produced and excluded within culture, both inside and outside its borders. This approach is contrasted with more sociological studies of sexuality (labeling theory, social constructionism). Whereas queer theory investigates the relations between heterosexuality and homosexuality, sociologists tend to examine homosexual identities and communities, paradoxically ignoring the social construction of heterosexuality. Poststructuralism can inform a sociological approach to sexuality by emphasizing the generative character of all sexual identities. A sociological study of sexuality which is informed by poststructuralism would examine the exclusions implicit in a heterosexual/homosexual opposition. In this process, bisexual and transgender identities can become viable cultural possibilities, and a broad-based political coalition established. Whereas mainstream sociology focuses on the ways in which homosexuals are outside social norms, and whereas queer theory exploits the ways in which this outside is already inside, this perspective suggests that a critical sexual politics seeks to move beyond an inside/outside model.
Keywords: LGBTQIA2+; approches et analyses; cours; discipline; méthodologie; post-structuralisme; premier cycle; queer; sciences humaines; sexualité; soc2014; sociologie; thématiques

Femmes, action politique et identité - Sève, Micheline de (Cahiers de recherche sociologique, 1994)
Centré sur la différence de genre, le mouvement des femmes serait condamné à l’éclatement à mesure que les femmes échappent à leur cantonnement dans l’appartenance à une catégorie sociale opprimée pour gagner l’espace qu’offre une société démocratique égalitaire à l’expression pluraliste des composantes multiples de leur personnalité publique. Une approche phénoménologique, axée sur la valorisation des expériences de vie et de l’histoire partagées de femmes se réclamant d’une culture civique commune, permet à l’autrice d’espérer dégager une stratégie féministe parallèle fondée sur la prise en compte des positions variées de sujets-femmes en situation pour les rallier autour d’actions politiques à mener en commun.
Keywords: cours; cycles supérieurs; discipline; fem9000; genre; identités LGBTQIA2+; militance; mouvements des femmes*; ressource en ligne; science politique; science politique et droit; thématiques

The social construction of heterosexuality - Wilkinson, Sue; Kitzinger, Celia (Journal of Gender Studies, 1994)
Looks at some of the key issues raised by a tradition of social constructionist work on homosexuality, focusing on the nature of heterosexuality, heterosexual self-identification and the relationship between heterosexual sexual behavior and sexual identity. Political and theorectical importance of a sustained analysis of the functions and utility of heterosexuality; Impact of social constructionist theory on research relating to lesbians and gay men.
Keywords: 1900-1999; 1980-1989; 1990-1999; LGBTQIA2+; cours; discipline; histoire et politique; premier cycle; psychologie; périodes historiques; sciences humaines; soc2014; sociologie; thématiques